Battery and hydrogen-based electric vehicle adoption: A survey of Australian consumers perspective. Issue 4 (December 2022) - Loengbudnark, Wipa; Khalilpour, Kaveh; Bharathy, Gnana; Taghikhah, Firouzeh; Voinov, Alexey
Highlights: Results are based on a survey of 1735 consumers in Australia. EV-safety concern has a stronger impact on EV-adoption intention than the purchase cost and perceived benefits. Consumers' range sufficiency, tolerability in battery charging time, and fear of hydrogen explosion are the key preference factors for battery electric vehicles. Longer driving range is a key preference factor for hydrogen fuel cell electric vehicles. Abstract: Electric vehicles (EV) are a promising alternative for the current fossil-fuel-based vehicles. However, as of 2020, the share of EV sales was only 4.6 % globally, and 1 % in Australia. It is important to identify factors that promote or hinder consumer intentions of EV adoption. In addition, there are a few types of EVs, each with different advantages and disadvantages creating consumer segmentation. This study considered battery-powered EV and hydrogen fuel cell EV and sought to understand which factors influence the preferences for one of the two types of vehicles. We designed a survey on individual perceptions toward EV and collected data of 1735 consumers in Australia. Participants had a mean age of 44.9 years (SD = 16.71) and 41 % of them were males. The median daily traveling distances was 8.7 km, and 74 % of them reported using a personal car for commuting. The results show that the safety concern has a stronger impact on adoption intention than the purchase cost and perceived benefits. Age and consumers' current mode of transportation play a significant role in EV adoption intentions. In addition, the results indicate that preference for BEV is significantly affected by BEV range sufficiency, tolerability in battery charging time, and fear of hydrogen explosion, whereas the key preference factors for FCEVs is their longer driving range, and fear of battery explosion. Besides, the results reveal that part-time employees are more likely to prefer BEV than full-time workers. On the other hand, apartment residents tend to prefer FCEV more than people living in a house. Furthermore, female is more likely to still undecided than males whether they prefer BEV or FCEV.